Diagnóstico do cooperativismo agropecuário no Brasil - Santos, Sara Raquel de Barros (Universidade Federal de São Carlos, 2021)
This work aims to analyze the panorama of agricultural cooperatives in Brazil and its regions through the following variables: number of agricultural establishments; number of agricultural establishments organized in associations; number of agricultural establishments organized into cooperatives; technical guidance; use of fertilizers and pesticides. The research methodology is quantitative based on the collection and tabular analysis of secondary data present in the IBGE database based on data from the Agricultural Census of 2006 and 2017, where it was found that the regions that are most associated with cooperatives are the South, Southeast and Midwest regions and, consequently, are the ones that most benefit from this association. The Northeast and North regions, on the other hand, are those that least associate with cooperatives and those that least benefit from cooperatives. The data pointed out the need for incentives for the Northeast and North regions to associate more closely with cooperatives in order to strengthen agriculture in these regions. In addition, it was possible to observe a strong relationship between cooperatives and technical assistance, considering that the regions that most associated themselves with cooperatives were also the ones that received the most technical guidance and, consequently, those that used fertilizers and pesticides the most.
Diagnostic of agriculture cooperativism in Brazil
Keywords: Cooperativismo; Associativismo; Agropecuária; Censo Agropecuário; CIENCIAS SOCIAIS APLICADAS::ECONOMIA; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIAS AGRARIA E DOS RECURSOS NATURAIS